Hormone therapy in survivors of gynaecological and breast cancer. (October 2014) - Bregar, Amy; Taylor, Kristin; Stuckey, Ashley
<x xml:space="preserve">Abstract</x> Key content Gynaecological and breast cancers affect premenopausal and perimenopausal women at rates ranging 15–70% and treatment often causes the abrupt onset of menopause. Available studies do not show an increase in recurrence or decrease in survival among women with endometrial, ovarian or cervical cancer who use hormone replacement therapy (HRT). Data regarding the risks of systemic HRT in survivors of breast cancer are varied, and an increase in breast cancer recurrence with the use of systemic HRT has been demonstrated in randomised controlled trials. Limited data exist regarding the use of vaginal estrogen, however, no effect on recurrence has been demonstrated. The decision regarding the use of HRT in women with cancer must be individualised and should take into account issues regarding quality of life. Learning objectives To review the evidence regarding the cancer‐specific risks, that is, recurrence or death, of HRT in survivors of gynaecological and breast cancer. To provide recommendations for the use of HRT in survivors of gynaecological and breast cancer. Ethical issues How to balance the risks of HRT with quality of life concerns in survivors of gynaecological and breast cancer when evidence to guide our recommendations is limited?